2022
DOI: 10.3389/fphar.2022.1048653
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid concentrations of fluoroquinolones and carbapenems in tuberculosis meningitis

Abstract: Background: Tuberculosis meningitis (TBM) is the most lethal form of TB. It is difficult to treat in part due to poor or uncertain drug penetration into the central nervous system (CNS). To help fill this knowledge gap, we evaluated the cerebrospinal fluid (CSF) concentrations of fluoroquinolones and carbapenems in patients being treated for TBM.Methods: Serial serum and CSF samples were collected from hospitalized patients being treated for TBM. CSF was collected from routine lumbar punctures between alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Vaborbactam was shown to permeate the CSF fluid effectively in all the measurements, while meropenem was undetectable. However, the low CNS penetration of meropenem and substantial interindividual variability have already been observed in the literature [28][29][30][31]. Unfortunately, for our patient, it was not possible to conduct therapeutic drug monitoring (TDM) due to laboratory limitations throughout the hospital stay.…”
Section: Discussionmentioning
confidence: 85%
“…Vaborbactam was shown to permeate the CSF fluid effectively in all the measurements, while meropenem was undetectable. However, the low CNS penetration of meropenem and substantial interindividual variability have already been observed in the literature [28][29][30][31]. Unfortunately, for our patient, it was not possible to conduct therapeutic drug monitoring (TDM) due to laboratory limitations throughout the hospital stay.…”
Section: Discussionmentioning
confidence: 85%
“…Although brain tissue exposures for pyrazinamide are unknown in humans, PET imaging in non-human primates with a chemically identical radioanalog of pyrazinamide demonstrated excellent brain tissue exposures 35 , which were consistent with our data (mass spectrometry) from the mouse studies. Similarly, while moxi oxacin (Mx), active against several MDR strains of M. tuberculosis, has excellent CSF penetration 36,37 , brain tissue exposures are not known and our data from mouse studies demonstrated limited brain (tissue/plasma ratio 0.23) but excellent lung tissue penetration (tissue/plasma ratio 3.34). Overall, these data suggested that pretomanid and pyrazinamide based multidrug regimens could be highly effective in TB meningitis.…”
Section: Discussionmentioning
confidence: 86%
“…In our case Flavobacterium was resistant to sulfamethoxazole/trimethoprim, in contrast to other reported Flavobacteria , which were susceptible to this therapeutic agent. Based on the antimicrobial susceptibility testing with a low MIC and given the excellent central nervous system penetration of levofloxacin [ 12 ] , we chose this agent to treat the patient. Regarding duration of therapy, we treated the patient based on the guidelines for community acquired Gram-negative meningitis, according to which an antibiotic therapy of at least 21 days is recommended [ 1 ] .…”
Section: Discussionmentioning
confidence: 99%